The Performativity of Weaponized Language: Manipulation, Power, and Resistance - Drałus, Dorota; Wichłacz, Monika (Roczniki Nauk Społecznych, 2025)
This study explores weaponized communication—a strategic manipulation of language used to influence perceptions, emotions, and behavior while undermining democratic values and societal cohesion. Building on theories of speech acts by John L. Austin and John Searle, it examines how language’s performative nature is exploited to reshape realities, normalize exclusion, and disrupt public trust. Weaponized communication leverages modern technology to amplify cognitive overload, disinformation, and divisive narratives, marking a shift from traditional persuasion to emotion-driven, viral rhetoric. This transformation challenges ethical norms and raises concerns about language as a tool of coercion and oppression. The paper also links historical insights from Sophistic rhetoric and Confucian linguistic principles to contemporary issues like propaganda and hate speech. By analyzing these mechanisms, the study sheds light on the intersection of language, power, and societal change, emphasizing the urgent need for ethical discourse in the digital era.